ChemInform Abstract: Enantioselective Direct Aldol Reactions Promoted by Phosphine Oxide Aziridinyl Phosphonate Organocatalysts. Issue 16 (March 2016) - Dogan, Oezdemir; Tan, Duygu
Abstract: The phosphonate POAP is tested as a chiral catalyst in the aldol reaction of cyclohexanone with aldehydes (II), however, the yield, diastereoselectivity, and enantioselectivity are only low to moderate.